THE INFLUENCE OF GCG AND COMPANY SIZE ON FINANCIAL PERFORMANCE IN CIGARETTE COMPANIES LISTED ON THE IDX IN 2019-2023 - Rini, Dian Yustika; Hasanudin, Mohamad; Putri, Alvianita Gunawan (Applied Accounting and Management Review (AAMAR), 2024)
Financial performance is a measure that shows the financial health of a company during a certain period. Analyzing the influence of GCG and company size on financial performance is the purpose of this research. This study employs purposive sampling, with four companies serving as the sample. The data analysis technique uses multiple linear regression analysis, and the analysis technique to test the hypothesis uses the F test, t test, and the coefficient of determination test (R2). The results of hypothesis testing and discussion show that the Board of Directors, Independent Commissioner, Audit Committee, Institutional Ownership, and Company Size simultaneously affect financial performance. While partially the Independent Board of Commissioners has a significant effect on financial performance, while the Board of Directors, Audit Committee, Institutional Ownership, and Company Size have no significant effect on financial performance.  Keywords: Financial Performance (ROA), Board of Directors, Independent Commissioner, Institutional Ownership, Company Size.